5.1.53 Problems 5201 to 5300

Table 5.105: First order ode

#

ODE

Mathematica

Maple

10980

\[ {}y^{\prime } = -\frac {216 y \left (-2 y^{4}-3 y^{3}-6 y^{2}-6 y+6 x +6\right )}{2484 y^{6}+216 x^{3}-1296 x y+2808 y^{4}+1728 y^{3}-648 x y^{3}-648 x^{2} y+594 y^{7}-1296 y^{2}-1296 y+1080 y^{5} x +594 x y^{6}-432 y^{4} x -1944 x y^{2}-648 x^{2} y^{2}+72 y^{8} x +216 y^{7} x -216 x^{2} y^{4}-18 y^{8}+4428 y^{5}-324 x^{2} y^{3}-315 y^{9}-126 y^{10}-8 y^{12}-36 y^{11}} \]

10981

\[ {}y^{\prime } = \frac {\left (x y+1\right )^{3}}{x^{5}} \]

10982

\[ {}y^{\prime } = \frac {x \left (-x^{2}+2 x^{2} y-2 x^{4}+1\right )}{y-x^{2}} \]

10983

\[ {}y^{\prime } = y \left (y^{2}+y \,{\mathrm e}^{b x}+{\mathrm e}^{2 b x}\right ) {\mathrm e}^{-2 b x} \]

10984

\[ {}y^{\prime } = y^{3}-3 x^{2} y^{2}+3 x^{4} y-x^{6}+2 x \]

10985

\[ {}y^{\prime } = y^{3}+x^{2} y^{2}+\frac {x^{4} y}{3}+\frac {x^{6}}{27}-\frac {2 x}{3} \]

10986

\[ {}y^{\prime } = \frac {y \left (y^{2} x^{7}+x^{4} y+x -3\right )}{x} \]

10987

\[ {}y^{\prime } = y \left (y^{2}+{\mathrm e}^{-x^{2}} y+{\mathrm e}^{-2 x^{2}}\right ) {\mathrm e}^{2 x^{2}} x \]

10988

\[ {}y^{\prime } = \frac {y \left (y^{2}+x y+x^{2}+x \right )}{x^{2}} \]

10989

\[ {}y^{\prime } = \frac {y^{3}-3 x y^{2}+3 x^{2} y-x^{3}+x}{x} \]

10990

\[ {}y^{\prime } = \frac {x^{3} y^{3}+6 x^{2} y^{2}+12 x y+8+2 x}{x^{3}} \]

10991

\[ {}y^{\prime } = \frac {a^{3} x^{3} y^{3}+3 y^{2} a^{2} x^{2}+3 a x y+1+x \,a^{2}}{x^{3} a^{3}} \]

10992

\[ {}y^{\prime } = \frac {y \,{\mathrm e}^{-\frac {x^{2}}{2}} \left (2 y^{2}+2 y \,{\mathrm e}^{\frac {x^{2}}{4}}+2 \,{\mathrm e}^{\frac {x^{2}}{2}}+x \,{\mathrm e}^{\frac {x^{2}}{2}}\right )}{2} \]

10993

\[ {}y^{\prime } = \frac {y^{3}-3 x y^{2}+3 x^{2} y-x^{3}+x^{2}}{\left (x -1\right ) \left (1+x \right )} \]

10994

\[ {}y^{\prime } = \frac {y \left (x^{2} y^{2}+y x \,{\mathrm e}^{x}+{\mathrm e}^{2 x}\right ) {\mathrm e}^{-2 x} \left (x -1\right )}{x} \]

10995

\[ {}y^{\prime } = \frac {\left (x y+1\right ) \left (x^{2} y^{2}+x^{2} y+2 x y+1+x +x^{2}\right )}{x^{5}} \]

10996

\[ {}y^{\prime } = \frac {y^{3}-3 x y^{2} \ln \left (x \right )+3 x^{2} \ln \left (x \right )^{2} y-x^{3} \ln \left (x \right )^{3}+x^{2}+x y}{x^{2}} \]

10997

\[ {}y^{\prime } = -F \left (x \right ) \left (-a \,x^{2}+y^{2}\right )+\frac {y}{x} \]

10998

\[ {}y^{\prime } = -F \left (x \right ) \left (y^{2}-2 x y-x^{2}\right )+\frac {y}{x} \]

10999

\[ {}y^{\prime } = -F \left (x \right ) \left (-y^{2} a -b \,x^{2}\right )+\frac {y}{x} \]

11000

\[ {}y^{\prime } = -F \left (x \right ) \left (-y^{2}+2 x^{2} y+1-x^{4}\right )+2 x \]

11001

\[ {}y^{\prime } = -F \left (x \right ) \left (-y^{2}+2 x y+x^{2}\right )+\frac {y}{x} \]

11002

\[ {}y^{\prime } = -F \left (x \right ) \left (-7 x y^{2}-x^{3}\right )+\frac {y}{x} \]

11003

\[ {}y^{\prime } = -F \left (x \right ) \left (-y^{2}-2 y \ln \left (x \right )-\ln \left (x \right )^{2}\right )+\frac {y}{\ln \left (x \right ) x} \]

11004

\[ {}y^{\prime } = -x^{3} \left (-y^{2}-2 y \ln \left (x \right )-\ln \left (x \right )^{2}\right )+\frac {y}{\ln \left (x \right ) x} \]

11005

\[ {}y^{\prime } = \left (y-{\mathrm e}^{x}\right )^{2}+{\mathrm e}^{x} \]

11006

\[ {}y^{\prime } = \frac {\left (y-\operatorname {Si}\left (x \right )\right )^{2}+\sin \left (x \right )}{x} \]

11007

\[ {}y^{\prime } = \left (y+\cos \left (x \right )\right )^{2}+\sin \left (x \right ) \]

11008

\[ {}y^{\prime } = \frac {\left (y-\ln \left (x \right )-\operatorname {Ci}\left (x \right )\right )^{2}+\cos \left (x \right )}{x} \]

11009

\[ {}y^{\prime } = \frac {\left (y-x +\ln \left (1+x \right )\right )^{2}+x}{1+x} \]

11010

\[ {}y^{\prime } = \frac {2 x^{2} y+x^{3}+y \ln \left (x \right ) x -y^{2}-x y}{x^{2} \left (x +\ln \left (x \right )\right )} \]

12001

\[ {}y^{\prime } = f \left (x \right ) \]

12002

\[ {}y^{\prime } = f \left (y\right ) \]

12003

\[ {}y^{\prime } = f \left (x \right ) g \left (y\right ) \]

12004

\[ {}g \left (x \right ) y^{\prime } = f_{1} \left (x \right ) y+f_{0} \left (x \right ) \]

12005

\[ {}g \left (x \right ) y^{\prime } = f_{1} \left (x \right ) y+f_{n} \left (x \right ) y^{n} \]

12006

\[ {}y^{\prime } = f \left (\frac {y}{x}\right ) \]

12007

\[ {}y^{\prime } = y^{2} a +b x +c \]

12008

\[ {}y^{\prime } = y^{2}-a^{2} x^{2}+3 a \]

12009

\[ {}y^{\prime } = y^{2}+a^{2} x^{2}+b x +c \]

12010

\[ {}y^{\prime } = y^{2} a +b \,x^{n} \]

12011

\[ {}y^{\prime } = y^{2}+a n \,x^{n -1}-a^{2} x^{2 n} \]

12012

\[ {}y^{\prime } = y^{2} a +b \,x^{2 n}+c \,x^{n -1} \]

12013

\[ {}y^{\prime } = a \,x^{n} y^{2}+b \,x^{-n -2} \]

12014

\[ {}y^{\prime } = a \,x^{n} y^{2}+b \,x^{m} \]

12015

\[ {}y^{\prime } = y^{2}+k \left (a x +b \right )^{n} \left (c x +d \right )^{-n -4} \]

12016

\[ {}y^{\prime } = a \,x^{n} y^{2}+b m \,x^{m -1}-a \,b^{2} x^{n +2 m} \]

12017

\[ {}y^{\prime } = \left (a \,x^{2 n}+b \,x^{n -1}\right ) y^{2}+c \]

12018

\[ {}\left (a_{2} x +b_{2} \right ) \left (y^{\prime }+\lambda y^{2}\right )+a_{0} x +b_{0} = 0 \]

12019

\[ {}x^{2} y^{\prime } = a \,x^{2} y^{2}+b \]

12020

\[ {}x^{2} y^{\prime } = x^{2} y^{2}-a^{2} x^{4}+a \left (1-2 b \right ) x^{2}-b \left (b +1\right ) \]

12021

\[ {}x^{2} y^{\prime } = a \,x^{2} y^{2}+b \,x^{n}+c \]

12022

\[ {}x^{2} y^{\prime } = x^{2} y^{2}+a \,x^{2 m} \left (b \,x^{m}+c \right )^{n}-\frac {n^{2}}{4}+\frac {1}{4} \]

12023

\[ {}\left (c_{2} x^{2}+b_{2} x +a_{2} \right ) \left (y^{\prime }+\lambda y^{2}\right )+a_{0} = 0 \]

12024

\[ {}x^{4} y^{\prime } = -y^{2} x^{4}-a^{2} \]

12025

\[ {}a \,x^{2} \left (x -1\right )^{2} \left (y^{\prime }+\lambda y^{2}\right )+b \,x^{2}+c x +s = 0 \]

12026

\[ {}\left (a \,x^{2}+b x +c \right )^{2} \left (y^{\prime }+y^{2}\right )+A = 0 \]

12027

\[ {}x^{n +1} y^{\prime } = a \,x^{2 n} y^{2}+c \,x^{m}+d \]

12028

\[ {}\left (a \,x^{n}+b \right ) y^{\prime } = b y^{2}+a \,x^{n -2} \]

12029

\[ {}\left (a \,x^{n}+b \,x^{m}+c \right ) \left (y^{\prime }-y^{2}\right )+a n \left (n -1\right ) x^{n -2}+b m \left (m -1\right ) x^{m -2} = 0 \]

12030

\[ {}y^{\prime } = y^{2} a +b y+c x +k \]

12031

\[ {}y^{\prime } = y^{2}+a \,x^{n} y+a \,x^{n -1} \]

12032

\[ {}y^{\prime } = y^{2}+a \,x^{n} y+b \,x^{n -1} \]

12033

\[ {}y^{\prime } = y^{2}+\left (\alpha x +\beta \right ) y+a \,x^{2}+b x +c \]

12034

\[ {}y^{\prime } = y^{2}+a \,x^{n} y-a b \,x^{n}-b^{2} \]

12035

\[ {}y^{\prime } = -\left (n +1\right ) x^{n} y^{2}+a \,x^{n +m +1}-a \,x^{m} \]

12036

\[ {}y^{\prime } = a \,x^{n} y^{2}+b \,x^{m} y+b c \,x^{m}-a \,c^{2} x^{n} \]

12037

\[ {}y^{\prime } = a \,x^{n} y^{2}-a \,x^{n} \left (b \,x^{m}+c \right ) y+b m \,x^{m -1} \]

12038

\[ {}y^{\prime } = -a n \,x^{n -1} y^{2}+c \,x^{m} \left (a \,x^{n}+b \right ) y-c \,x^{m} \]

12039

\[ {}y^{\prime } = a \,x^{n} y^{2}+b \,x^{m} y+c k \,x^{k -1}-b c \,x^{m +k}-a \,c^{2} x^{n +2 k} \]

12040

\[ {}x y^{\prime } = y^{2} a +b y+c \,x^{2 b} \]

12041

\[ {}x y^{\prime } = y^{2} a +b y+c \,x^{n} \]

12042

\[ {}x y^{\prime } = y^{2} a +\left (n +b \,x^{n}\right ) y+c \,x^{2 n} \]

12043

\[ {}x y^{\prime } = x y^{2}+a y+b \,x^{n} \]

12044

\[ {}x y^{\prime }+a_{3} x y^{2}+a_{2} y+a_{1} x +a_{0} = 0 \]

12045

\[ {}x y^{\prime } = a \,x^{n} y^{2}+b y+c \,x^{-n} \]

12046

\[ {}x y^{\prime } = a \,x^{n} y^{2}+m y-a \,b^{2} x^{n +2 m} \]

12047

\[ {}x y^{\prime } = x^{2 n} y^{2}+\left (m -n \right ) y+x^{2 m} \]

12048

\[ {}x y^{\prime } = a \,x^{n} y^{2}+b y+c \,x^{m} \]

12049

\[ {}x y^{\prime } = a \,x^{2 n} y^{2}+\left (b \,x^{n}-n \right ) y+c \]

12050

\[ {}x y^{\prime } = a \,x^{2 n +m} y^{2}+\left (b \,x^{n +m}-n \right ) y+c \,x^{m} \]

12051

\[ {}\left (a_{2} x +b_{2} \right ) \left (y^{\prime }+\lambda y^{2}\right )+\left (a_{1} x +b_{1} \right ) y+a_{0} x +b_{0} = 0 \]

12052

\[ {}\left (a x +c \right ) y^{\prime } = \alpha \left (b x +a y\right )^{2}+\beta \left (b x +a y\right )-b x +\gamma \]

12053

\[ {}2 x^{2} y^{\prime } = 2 y^{2}+x y-2 x \,a^{2} \]

12054

\[ {}2 x^{2} y^{\prime } = 2 y^{2}+3 x y-2 x \,a^{2} \]

12055

\[ {}x^{2} y^{\prime } = a \,x^{2} y^{2}+b x y+c \]

12056

\[ {}x^{2} y^{\prime } = c \,x^{2} y^{2}+\left (a \,x^{2}+b x \right ) y+\alpha \,x^{2}+\beta x +\gamma \]

12057

\[ {}x^{2} y^{\prime } = a \,x^{2} y^{2}+b x y+c \,x^{n}+s \]

12058

\[ {}x^{2} y^{\prime } = a \,x^{2} y^{2}+b x y+c \,x^{2 n}+s \,x^{n} \]

12059

\[ {}x^{2} y^{\prime } = c \,x^{2} y^{2}+\left (a \,x^{n}+b \right ) x y+\alpha \,x^{2 n}+\beta \,x^{n}+\gamma \]

12060

\[ {}x^{2} y^{\prime } = \left (\alpha \,x^{2 n}+\beta \,x^{n}+\gamma \right ) y^{2}+\left (a \,x^{n}+b \right ) x y+c \,x^{2} \]

12061

\[ {}\left (x^{2}-1\right ) y^{\prime }+\lambda \left (y^{2}-2 x y+1\right ) = 0 \]

12062

\[ {}\left (a \,x^{2}+b \right ) y^{\prime }+\alpha y^{2}+\beta x y+\frac {b \left (a +\beta \right )}{\alpha } = 0 \]

12063

\[ {}\left (a \,x^{2}+b \right ) y^{\prime }+\alpha y^{2}+\beta x y+\gamma = 0 \]

12064

\[ {}\left (a \,x^{2}+b \right ) y^{\prime }+y^{2}-2 x y+\left (1-a \right ) x^{2}-b = 0 \]

12065

\[ {}\left (a \,x^{2}+b x +c \right ) y^{\prime } = y^{2}+\left (2 \lambda x +b \right ) y+\lambda \left (\lambda -a \right ) x^{2}+\mu \]

12066

\[ {}\left (a \,x^{2}+b x +c \right ) y^{\prime } = y^{2}+\left (a x +\mu \right ) y-\lambda ^{2} x^{2}+\lambda \left (b -\mu \right ) x +\lambda c \]

12067

\[ {}\left (a_{2} x^{2}+b_{2} x +c_{2} \right ) y^{\prime } = y^{2}+\left (a_{1} x +b_{1} \right ) y-\lambda \left (\lambda +a_{1} -a_{2} \right ) x^{2}+\lambda \left (b_{2} -b_{1} \right ) x +\lambda c_{2} \]

12068

\[ {}\left (a_{2} x^{2}+b_{2} x +c_{2} \right ) y^{\prime } = y^{2}+\left (a_{1} x +b_{1} \right ) y+a_{0} x^{2}+b_{0} x +c_{0} \]

12069

\[ {}\left (x -a \right ) \left (x -b \right ) y^{\prime }+y^{2}+k \left (y+x -a \right ) \left (y+x -b \right ) = 0 \]